Assessment on The Potential of Plastics Biodegradation by Termites (Dictyoptera: Isoptera) - Aisha Shahirah binti Azli (2024)
This thesis was based on the objectives which indicate to assess the potential of plastics biodegradation among termites and to compare the plastics preferences and biodegradation rates by termites, specifically forpolypropylene (PP), polyethylene (PE), polyethylene terephthalate (PET), polystyrene(PS), and polyvinyl chloride (PVC). This study also investigate dat the termites' capacity to biodegrade five different kinds of plastic over the course of five days.In order to determine the decrease percentages and evaluate the rates of biodegradation, the initial and end weights of every type of plastic were measured. Plastics such as PP, PE, PET, PS, and PVC were evaluated. The results showed that different plastics biodegraded to differing degrees. With an 84.42% weight reduction, polyvinyl chloride(PVC) had the highest biodegradation rate. Significant degradation was also demonstrated by polyethylene(PE)and polyethylene terephthalate (PET), with reduction rates of 79.52% and 79.35%, respectively. Polypropylene(PP) displayed the lowest biodegradation rate at 58.51%, while polystyrene(PS) demonstrated a moderate reduction rate of 64.04%. According to the study, termites have the ability to biodegrade specific plastics, with PVC being the most vulnerable and PE and PET following closely behind. Even so, the degradation rates of PS and PP were lower. These findings demonstrate the various polymers' susceptibilities to termite biodegradation and imply the potential use of termites in biological waste management plans, especially for more biodegradable plastics like PET, PVC, and PE. It is advised to conduct more research to examine the biochemical processes underlying termite-mediated biodegradation as well as to assess the environmental effects and long-term viability of employing termites to handle plastic waste.